Electronic Measurements and Instrumentation - U.A.BAKSHI. ([S.l.] : Technical Publications, 2004)
Basic Measurement Concepts Measurement systems - Static and dynamic characteristics - Units and standards of measurements - Error :- Accuracy and precision, Types, Statistical analysis - Moving coil, Moving iron meters - Multimeters - Bridge measurements : - Maxwell, Hay, Schering, Anderson and Wien bridge. Basic Electronic Measurements Electronic multimeters - Cathode ray oscilloscopes - Block schematic - Applications - Special oscilloscopes :- Delayed time base oscilloscopes, Analog and digital storage oscilloscope, Sampling oscilloscope - Q meters - Vector meters - RF voltage and power measurements - True RMS meters. Signal Generators and Analyzers Function generators - Pulse and square wave generators, RF signal generators - Sweep generators - Frequency synthesizer - Wave analyzer - Harmonic distortion analyzer - Spectrum analyzer :- Digital spectrum analyzer, Vector network analyzer - Digital L,C,R measurements, Digital RLC meters. Digital Instruments Comparison of analog and digital techniques - Digital voltmeter - Multimeters - Frequency counters - Measurement of frequency and time interval - Extension of frequency range - Automation in digital instruments, Automatic polarity indication, Automatic ranging, Automatic zeroing, Fully automatic digital instruments, Computer controlled test systems, Virtual instruments. Data Acquisition Systems and Fiber Optic Measurements Elements of a digital data acquisition system - Interfacing of transducers - Multiplexing - Data loggers - Computer controlled instrumentation - IEEE 488 bus - Fiber optic measurements for power and system loss - Optical time domains reflectometer.
Keywords: Electronic measurements; Electronic instruments